Lead potential bioaccumulation in two species of commonly used medicinal plants in Leyte - Ongy, Honeylene V.; Belonias, Beatriz S. (Annals of Tropical Research, 2018)
Medicinal plants, especially those that are grown and cultivated in heavily polluted soils, are one source of lead toxicity in humans. This study assessed the Pb accumulation capacity of two commonly used medicinal plants, Artemisia vulgaris and Plectranthus amboinicus. Bioaccumulation factor, translocation factor and metal extraction ratio of each plant species were also determined. The plants were planted in pots in a controlled experiment and subjected to different concentrations of Pb (0–600ppm) for 4 weeks. Both plants showed no visual signs of Pb toxicity at the end of the study. The growth of A. vulgaris was not significantly affected by the different levels of Pb added to the soil. The increase in height of P. amboinicus was significantly affected by the Pb in the soil. The roots accumulated more Pb, followed by the leaves and the stems. Pb level in plant tissues increased with increased addition of Pb to the soil. Bioaccumulation factor (BAF) of A. vulgaris and P. amboinicus was above 1 which means these plants are accumulators of Pb. With a translocation factor (TF) > 1, A. vulgaris can effectively transfer Pb from the stems to the shoots while P. amboinicus cannot. Of the two plants, P. amboinicus was most effective in removing lead from the soil even at high concentrations (600ppm).